Coyotes take advantage of ungulate carrion subsidies as wolves recolonize Washington ... - Malesis, Anna; Windell, Rebecca; Vanbianci, Carmen; Prugh, Laura (Dryad, 2024)
Apex predators exert suppressive effects on mesocarnivores; however, they also provide important carrion subsidies. Optimal foraging theory predicts that individuals respond to resource competition by using high value resources, while competition theory predicts that individuals respond by partitioning resources. This study investigated how the return of wolves (Canis lupus Linneas, 1758) to Washington state impacted the diet of a subordinate carnivore - the coyote (Canis latrans Say, 1823). We collected coyote scats from two areas of northern Washington with differing wolf densities and used traditional analysis of undigested remains to infer diet. We tested for differences in the volumes of prey categories, the proportion of ungulate prey that was scavenged, and diet diversity between seasons, study sites, and inside and outside of wolf pack territories. Coyote scats contained more adult ungulate remains inside of wolf pack territories (27%) compared to outside (14%), while seeds and berries were more ... : Coyote (Canis latrans) scats were collected from two sites in northern Washington, USA. Scats were primarily collected from transects that were surveyed monthly, with additional scats collected opportunistically at both sites during winter (January to March) 2018, summer (mid-June to mid-September) 2018, and winter (January to March) 2019. Scats were stored frozen, sterilized at -80 degrees Celsius for two weeks, and then species of origin was determined by molecular analysis of mitochondrial DNA. Scats attributed to coyotes were washed until only undigested remains were left and allowed to air dry. To identify diet items, any hair, bones, teeth or claws were compared to a reference collection of skins, skulls, and hairs of all mammal species occurring in the study area, as well as to identification guides. In addition, medulla casts, hair length, color pattern, and diameter, which was measured at the mid-point of the hairs with the Nurugo Micro Smartphone Microscope, were also used to help identify species ...